A Historiographical Overview of the University of Alcalá de Henares - Gómez-Cornejo Aguado, Omar (CIAN-Revista de Historia de las Universidades, 2018)
The aim of this paper is to know the historiographical overview of the University of Alcalá de Henares through the study of the monographs which exist about it. From the sixteenth century to nowadays numerous works have been published and the majority of them have been taken into account in this article. However, the attention has been focused on the study of the main themes which have been analysed during this time. Likewise, it is tried to detect and develop new approaches and perspectives, so potential aspects in the research of this University are also considered.
Keywords: Alcalá de Henares; history of universities; historiography; bibliography; monographs